Antioxidant Activity of Spent Coffee Ground Extracts Toward Soybean Oil and Fish Oil. Issue 4 (25th February 2019) - Hwang, Hong‐Sik; Winkler‐Moser, Jill K.; Kim, Youngmok; Liu, Sean X.
Abstract : Although studies have shown that spent coffee ground (SCG) extracts have antioxidant activity, no systematic study has been reported under actual storage conditions. The purpose of this study is to estimate the feasibility of practical application of SCG extracts as natural antioxidants for soybean oil and fish oil. An ethanol extract (EE), an acetone extract (AE), and polar compounds isolated from oil (PCO) are prepared and their activity is compared to a synthetic antioxidant, butylated hydroxytoluene (BHT). EE shows the strongest radical scavenging activity for 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radicals and the highest total phenolic content (TPC) followed by AE and then PCO. However, during storage of soybean oil and fish oil at 35 and 50 °C, AE has the strongest antioxidant activity as determined by peroxide value, conjugated diene value, p ‐anisidine value, and headspace volatile analyses. In soybean oil, 0.25% AE has antioxidant activity that is equal to or better than 0.02% BHT. In fish oil, the antioxidant activity of 0.25% AE is inferior to that of 0.02% BHT. However, increased concentrations of AE show improved antioxidant activity. This study shows that SCG extracts can be practically used as natural antioxidants for vegetable oils and omega‐3 oils. Practical Application : Due to lack of information about the antioxidant activity of spent coffee ground (SCG) extracts, this study is specifically aimed and designed to provide information on their activity toward soybean oil and fish oil during actual storage. This study shows that 0.25% acetone extract has equal or better protective effects than BHT in soybean oil at 35 and 50 °C. The activity is further improved with increasing concentration. The activity of the acetone extract in fish oil is not as strong as in soybean oil, but higher concentrations further improve the antioxidant activity. In this study, it is clearly demonstrated that the SCG extracts can have practical use as natural antioxidants for vegetable oils and oils with high concentration of omega‐3 fatty acids. Among spent coffee ground (SCG) extracts, the acetone extract (AE) has the strongest antioxidant activity. In soybean oil, 0.25% AE has antioxidant activity that is equal to or better than 0.02% butylated hydroxytoluene (BHT). This study shows that SCG extracts can be practically used as natural antioxidants for edible oils. Abstract : Among spent coffee ground (SCG) extracts, the acetone extract (AE) has the strongest antioxidant activity. In soybean oil, 0.25% AE has antioxidant activity that is equal to or better than 0.02% butylated hydroxytoluene (BHT). This study shows that SCG extracts can be practically used as natural antioxidants for edible oils.